STRATEGY OF IMPLEMENTING DIFFERENTIATED LEARNING IN THE MATERIAL OF CITIZENS' INDEPENDENCE IN THE COURSE OF PANCASILA AND CITIZENSHIP EDUCATION AT SMP NEGERI 1 SAMARINDA: Mixed Method Study at SMP Negeri 1 Samarinda - Hidayah Nur Asmara Asmara; Jawatir Pardosi Pardosi; Asnar Asnar; Suryaningsi Suryaningsi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Each student has different potential and learning needs, so the application of differentiated learning is important to create an inclusive and meaningful learning process. The purpose of this study was to determine how the implementation of diagnostic tests at SMP Negeri 1 Samarinda, then to determine the implementation of differentiated learning based on content, process and product in the material of citizen freedom of opinion at SMP Negeri 1 Samarinda. And to analyze the specific strategies used by teachers in implementing differentiated learning on the material of citizen freedom of opinion in PPKn lessons at SMP Negeri 1 Samarinda. The approach used is a mixed method with a sequential explanatory design model, where quantitative data is collected first through diagnostic tests to measure students' learning readiness, then continued with qualitative data collection through observation, in-depth interviews, and documentation to deepen understanding of the learning strategies applied. The results of the diagnostic test showed that 17% of students were in the low readiness category, 35% were moderate, and 48% were high, which became the basis for teachers in implementing differentiated learning. Teachers apply process, content, and product differentiation strategies, which are adjusted to students' readiness and learning profiles. This learning increases active participation, understanding of the material, and democratic attitudes of students.